2021
DOI: 10.5603/ep.a2021.0053
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced diabetes

Abstract: Pembrolizumab-induced diabetesPembrolizumab, a checkpoint inhibitor, has improved the prognosis of advanced malignancies such as malignant melanoma [1]. Programmed cell death protein 1 (PD-1) is a negative regulator of T-cell activation, generally expressed on chronically activated T cells, especially CD8+ T cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Other studies showed that common cancer-fighting program death 1 (PD-1) and program death ligand 1 (PDL-1) inhibitors have been shown to have numerous autoimmune endocrine side effects such as drug-induced T1DM [ 12 , 13 ]. Pembrolizumab, a humanized monoclonal antibody against PD-1 used in the treatment of common cancers such as melanoma, lung cancer, and Hodgkin lymphoma, is one such example of a drug that was implicated in the induction of T1DM [ 14 ]. In these instances, the prescribed theory attributes the induction of autoimmune destruction of endogenous hormones to the drugs’ capability to bind off-target tissue or hormone epitopes, which produces the undesired side effect [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that common cancer-fighting program death 1 (PD-1) and program death ligand 1 (PDL-1) inhibitors have been shown to have numerous autoimmune endocrine side effects such as drug-induced T1DM [ 12 , 13 ]. Pembrolizumab, a humanized monoclonal antibody against PD-1 used in the treatment of common cancers such as melanoma, lung cancer, and Hodgkin lymphoma, is one such example of a drug that was implicated in the induction of T1DM [ 14 ]. In these instances, the prescribed theory attributes the induction of autoimmune destruction of endogenous hormones to the drugs’ capability to bind off-target tissue or hormone epitopes, which produces the undesired side effect [ 15 ].…”
Section: Discussionmentioning
confidence: 99%